Comparative Prostate Cancer Detection Rate of Transrectal Ultrasonography Guided versus Finger Guided Prostate Biopsy - Rizki Abri Laksono; Tanaya Ghinorawa; Aria Danurdoro (Indonesian Journal of Cancer, 2023)
Background: Prostate biopsy was used to diagnose and establish a therapy for prostate cancer (PCa). Instead of using conventional finger-guided prostate biopsy (FGPB) to approximate prostatic architecture, transrectal ultrasonography-guided biopsies of the prostate (TRUSGB) have become more popular nowadays because of offer direct visualization. However, the lack of availability of transrectal ultrasound probes in less-developed regions raises concerns regarding the need to diagnose patients with PCa. Moreover, different conclusions have been found from prior studies that examined the efficacy of both methods. This study aims to compare the accuracy of TRUSGB to FGPB in prostate cancer.. Methods: This study was done retrospectively from 50 medical records of PCa in the Urology Division of Sardjito Hospital from January 2009 until December 2013. Patients’ age, PSA value, digital rectal examination, and histopathological examination were analyzed. Results: The mean age was 65.18 ± 7.76 years in FGPB and 67.52 ± 10.79 years in TRUSGB group. The median PSA was 65.01 (range: 16.33–114.72) ng/mL in FGPB and 71.75 (range: 19.86– 123.47) ng/mL in TRUSGB. Abnormal DRE was found in 75.75% of patients in FGPB group and 70.58% in TRUSGB. Comparable cancer detection rates were found in the FGPB and TRUSGB groups (45.45% vs. 52.94%) (p = 0.136).Conclusions: The cancer detection rates for FGPB and TRUSGB procedures are comparable. This supports using FGPB as the first-line diagnostic technique, especially in low-resource situations where ultrasonography is unavailable.